The Impact of Theological Interpretations on Divorces within Muslim Families in Makassar City, Indonesia - Abdullah, Abdullah; Nurhayati, Nurhayati; Natsif, Fadli Andi; Siddik, Hasbi; Fathurrahman, Fathurrahman (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
In Makassar City, located in South Sulawesi, one of the contributing factors to divorce is the level of theological comprehension or grasp of the teachings of the Islamic faith. Comprehension of the theology can shape perspectives on the duties of the husband and the wife within the marriage institution. This study employs a qualitative-empirical methodology using a theology of law framework. Theology of law is a methodological approach in Islamic studies that focuses on integrating and interconnecting many aspects. The data was gathered through comprehensive interviews and analysis of documents. The informants interviewed were husband and wife who had divorced. The research findings indicate a robust correlation between theology and the Islamic law. An individual with a moderate and contextual theological comprehension will likewise possess a flexible and moderate comprehension of the Islamic legislation. Conversely, an individual with a limited and inflexible comprehension of theology will interpret the Islamic law based on the Qur’an and likely have extremist perspectives. Moreover, the incidence of divorce is a manifestation of Allah SWT's decree or fate. In Jabariyah theology, the acceptance of fate leads to a lack of initiative in pursuing settlement through the established religious courts. These theological reasons are not independent, but rather influenced by economic circumstances and inherited issues that contribute to conflict and discord, ultimately resulting in divorce. From a legal theology standpoint, it is important to highlight that an interpretation of theology that passively submits to and embraces destiny, without making any attempts at reconciliation, leads to divorce, resulting in a failure to effectively apply the Islamic law. According to the Islamic law, a divorce is preceded by a mediation process in a religious court, during which the husband and the wife are given the opportunity to carefully consider all the adverse consequences.